PEMBERIAN MARGA PADA PRIA ATAU WANITA BUKAN MASYARAKAT BATAK TOBA AKIBAT PERKAWINAN BEDA SUKU DI KABUPATEN BULELENG DITINJAU DARI HUKUM ADAT BATAK TOBA - abram purba; Ratna Artha Windari; Adnyani, Ni Ketut Sari (Jurnal Ilmu Hukum Sui Generis, 2025)
This research aims to find out and analyze related to (1) the basis for granting surnames to women from other tribes according to customary law; (2) Procedures for granting surnames to non-Toba Batak women due to inter-ethnic marriages in Buleleng Regency. This research is empirical legal research that uses observation, interviews and document studies. The legal materials used in this research are primary, secondary and tertiary legal materials which are useful for drawing conclusions relevant to the problems in this research. The results of the research show that (1) The basis for granting surnames to women and men from other tribes according to customary law is that there is a plural life of citizens today, the flexibility of Batak customary law, the existence of traditional community views based on customary law regarding ethnic differences, the influence inheritance in customary law, and changing an individual's position based on customary law (2) The procedure for granting surnames to non-Batak Toba women according to traditional experts/traditional elders in Singaraja is with the Mangain traditional ceremony and before the Mangain is carried out, approval and participation from the Tulang Party is required. and/or Amangboru.